Learning strategies in the corporate setting. - Gary J. Conti; Rita C. Kolody; Bobby Schneider (Adult Education Research Conference, 1997)
The learning strategies of financial planners with American Express were assessed with SKILLS. Results with this group of professionals confirm the distinct learning strategy groups uncovered in previous learning strategy research.